PENGARUH SUKU BUNGA TABUNGAN TERHADAP JUMLAH TABUNGAN PADA PD. BKK BREBES CABANG KERSANA KABUPATEN BREBES - Ulul Absor (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2018)
Abstraksi This study entitled The Effect of Interest on Savings on the Number of Savings in PD. BKK Brebes Kersana Branch Brebes Regency. The purpose to be achieved in this study is to find out whether the interest rate affects the amount of savings in PD. BKK Brebes Kersana Branch. While the hypothesis proposed in this study is presumed that interest rates significantly influence the amount of savings received at PD. BKK Brebes Kersana Branch. To find out the effect of interest rates on the amount of savings, a simple regression analysis tool is used with the formula y = a + bx. With the calculation using SPSS the regression equation is y = 13,644,140,414 -1,720,458,207x, meaning that the amount of savings is influenced by the interest rate. The constant is 13,644,140,414. While the sign